Wnt-11 and Fz7 reduce cell adhesion in convergent extension by sequestration of PAPC and C-cadherin - Kraft, Bianca; Berger, Corinna D.; Steinbeisser, Herbert (The journal of cell biology, 2012)
Wnt-11/planar cell polarity signaling polarizes mesodermal cells undergoing convergent extension during Xenopus laevis gastrulation. These shape changes associated with lateral intercalation behavior require a dynamic modulation of cell adhesion. In this paper, we report that Wnt-11/frizzled-7 (Fz7) controls cell adhesion by forming separate adhesion-modulating complexes (AMCs) with the paraxial protocadherin (PAPC; denoted as AMCP) and C-cadherin (denoted as AMCC) via distinct Fz7 interaction domains. When PAPC was part of a Wnt-11-Fz7 complex, its Dynamin1- and clathrin-dependent internalization was blocked. This membrane stabilization of AMCP (Fz7/PAPC) by Wnt-11 prevented C-cadherin clustering, resulting in reduced cell adhesion and modified cell sorting activity. Importantly, Wnt-11 did not influence C-cadherin internalization; instead, it promoted the formation of AMCC (Fz7/Cadherin), which competed with cis-dimerization of C-cadherin. Because PAPC and C-cadherin did not directly interact and did not form a joint complex with Fz7, we suggest that Wnt-11 triggers the formation of two distinct complexes, AMCC and AMCP, that act in parallel to reduce cell adhesion by hampering lateral clustering of C-cadherin.